Assessment in Saskatchewan: Examining Provincial Approaches to Contemporary Assessment Principles through School Division Administrative Policies - Hebert, Cristyne; LeNouail, Kent (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2023)
In Saskatchewan, school divisions have been largely tasked with creating classroom-based assessment policy as, until very recently, the province lacked a current, Ministry-produced guiding document. Using an inductive and qualitative approach to summative content analysis, informed by a policy analysis framework, this project focused on school division administrative policies (n=26) to ascertain their alignment with contemporary assessment principles. Three principles—standards-based assessment, reliability and validity, and fairness and equity—and seven sub-principles—ongoing/continuous, transparent, (involves) stakeholders, (excludes) extraneous/arbitrary factors, triangulation, differentiation, and inclusion—served as the focus of analysis, with particular attention given to how clearly and consistently principles were addressed.